1983
DOI: 10.1080/15287398309530467
|View full text |Cite
|
Sign up to set email alerts
|

In vivoscreening of potential antidotes for chronic cadmium intoxication

Abstract: Nineteen chelating agents have been screened under identical conditions of metal loading in an attempt to establish their relative ability to mobilize cadmium from the liver and kidney in mice with chronic cadmium intoxication. The compounds investigated were divided into five groups: polyaminocarboxylic acids, monothiols, dithiols, macrocycles, and a miscellaneous category. Only 2,3-dimercaptopropanol (BAL) and sodium diethyldithiocarbamate (NaDDTC) were able to produce a statistically significant (at the 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Among dithiocarbamates, the compounds containing only nonpolar groups in addition to the dithiocarbamate group (CS 2 Na) have an intrinsic level of toxicity that is significantly greater than that of the compounds that are either amphipathic or those that contain polar groups. The results as a whole support the reports from previous screening studies (Cantilena and Klaassen, 1982;Shinobu et al, 1983) in which few of the many types of chelating agents examined showed any significant ability to mobilize cadmium from animals when the interval between cadmium administration and chelate treatment was longer than 24 h. The data presented here show not only that one must have the proper type of chelating group, but also that the presence of appropriate additional groups in the molecule is essential for an appreciable level of efficacy. Compounds fail when they contain groups that result in their being too polar (e.g., 2,3-dimercaptobutan-1,4-diol) or too nonpolar.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among dithiocarbamates, the compounds containing only nonpolar groups in addition to the dithiocarbamate group (CS 2 Na) have an intrinsic level of toxicity that is significantly greater than that of the compounds that are either amphipathic or those that contain polar groups. The results as a whole support the reports from previous screening studies (Cantilena and Klaassen, 1982;Shinobu et al, 1983) in which few of the many types of chelating agents examined showed any significant ability to mobilize cadmium from animals when the interval between cadmium administration and chelate treatment was longer than 24 h. The data presented here show not only that one must have the proper type of chelating group, but also that the presence of appropriate additional groups in the molecule is essential for an appreciable level of efficacy. Compounds fail when they contain groups that result in their being too polar (e.g., 2,3-dimercaptobutan-1,4-diol) or too nonpolar.…”
Section: Discussionsupporting
confidence: 92%
“…The commonly used water-soluble chelating agents such as EDTA, DPTA, and similar compounds have, at most, a very slight effect on the cadmium present in such deposits, though they are effective in antagonizing acute toxic effects of injected cadmium salts (Rau et al, 1987;Cantilena and Klaassen, 1982;Eybl et al, 1965), because these chelating agents cannot gain access to cadmium bound to intracellular sites (Waalkes et al, 1983). In fact, it is generally stated that most of the commonly used watersoluble chelating agents are completely unable to remove cadmium from the intracellular deposits that result from chronic cadmium intoxication (Cantilena and Klaassen, 1981;Shinobu et al, 1983;Eybl et al, 1988).…”
Section: Introductionmentioning
confidence: 96%
“…Sodium 2,3-dimercaptopropane-1 -sulfonate (DMPS), which is known to undergo active transport by these systems (Klotzbach & Diamond 1988), has repeatedly been shown to be ineffective for the mobilization of cadmium from its aged deposits (Bakka & Aaseth 1979;Von Berg & Smith 1980;Planas-Bohne & Lehmann 1983;Shinobu et al 1983). Sodium 2,3-dimercaptopropane-1 -sulfonate (DMPS), which is known to undergo active transport by these systems (Klotzbach & Diamond 1988), has repeatedly been shown to be ineffective for the mobilization of cadmium from its aged deposits (Bakka & Aaseth 1979;Von Berg & Smith 1980;Planas-Bohne & Lehmann 1983;Shinobu et al 1983).…”
Section: 7mentioning
confidence: 99%
“…One of the basic reasons for the seriousness of chronic cadmium toxicity is the rapid movement of ingested cadmium from extracellular sites, where it is amenable to reaction with chelating agents such as EDTA, to intracellular sites, where the cellular membrane prevents most of the commonly used chelating agents from gaining access to the firmly bound metal (Waalkes et al 1993). These include vicinal dithiols, such as 2,3-dimercapto-1-propanol (BAL) (Shaikh & Lucis 1972;Cherian 1980;Von Berg & Smith 1980), but not meso-2,3-dimercaptosuccinic acid (DMSA) (Bakka & Aaseth 1979;Gale et al 1983a;Planas-Bohne & Lehmann 1983;Shinobu et al 1983) nor sodium 2,3-dimercaptopropanesulfonate (DMPS) (Bakka & Aaseth 1979). These factommake the removal of cadmium from intracellular sites a problem with special features.…”
mentioning
confidence: 99%
“…However, some chelating agents administered repeatedly were able to mobilize Cd even when treatment was delayed following Cd exposure. This may be due to the easier access of the chelators to the intracellular bound Cd, owing to their lipophilic nature (Gale et al 1983;Shinobu et a/. 1983) and their ability to mobilize Cd even from Cd-MT (Cherian 1980;Cherian & Rodgers 1982).…”
Section: Introductionmentioning
confidence: 97%